End-Game : Apocalyptic Video Games, Contemporary Society, and Digital Media Culture - Alfonsin, Ben; Condis, Megan; Consalvo, Mia; Crossley, James; Crossley, James; DiTommaso, Lorenzo; DiTommaso, Lorenzo; Fielding-Redpath, Ellie; Fraser, Emma; Fuller, Samuel; Geraci, Jovi L.; Gibbons, William; et al. (Video Games and the Humanities ,, 2024)
Video games are a global phenomenon, international in their scope and democratic in their appeal. This is the first volume dedicated to the subject of apocalyptic video games. Its two dozen papers engage the subject comprehensively, from game design to player experience, and from the perspectives of content, theme, sound, ludic textures, and social function. The volume offers scholars, students, and general readers a thorough overview of this unique expression of the apocalyptic imagination in popular culture, and novel insights into an important facet of contemporary digital society.